2011
DOI: 10.4317/medoral.16.e593
|View full text |Cite
|
Sign up to set email alerts
|

Mesiodistal sizes and intermaxillary tooth-size ratios of two populations; Spanish and Peruvian. A comparative study

Abstract: Introduction: Adequate tooth-size ratios are required to ensure the satisfactory outcome of orthodontic treatment. Consequently, various methods of measuring tooth-size ratios have been developed being the Bolton ratio the most commonly accepted, known and used one. This ratio depending directly on mesiodistal tooth size has been associated with different ethnic backgrounds. Some authors suggest the need for specific standards for every population. Objectives: The objectives of our study were; to measure and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…This result was similar to that reported by Paredes et al (2011) andBrook et al (2009). Factors that can lead to this phenomenon are likely genetic, epigenetic and environmental infl uences.…”
Section: Discussionsupporting
confidence: 90%
“…This result was similar to that reported by Paredes et al (2011) andBrook et al (2009). Factors that can lead to this phenomenon are likely genetic, epigenetic and environmental infl uences.…”
Section: Discussionsupporting
confidence: 90%
“…The Japanese-Brazilian group showed significantly greater anterior and overall ratios than Bolton standards. Other studies also reported significantly greater anterior ratio 8,7,13,24 and overall ratio 6,13,25 than Bolton standards for different populations.…”
Section: Discussionmentioning
confidence: 82%
“…Despite its importance in the clinical setting to guide the orthodontist in cases with extreme tooth size discrepancies, Bolton's ratios have limitations, since the population and sex proportions of his sample were not specified, which implies potential selection bias 6 . There is evidence in the literature pointing towards ethnic differences in tooth size ratios [6][7][8] . It is reported that people with African ethnic backgrounds have larger teeth than do Japanese and Caucasians 9 .…”
Section: XXmentioning
confidence: 99%
“…Similar results were seen by Mahankudo et al in Karnataka population with anterior ratio 77.78% and overall ratio 92.005%. 23 The mean overall ratio in Spanish population was 91.97%, 24 Turkish population was 89.88, 25 Dominican…”
Section: Discussionmentioning
confidence: 99%